2014
DOI: 10.1186/1471-2407-14-383
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression patterns and clinical significance of estrogen receptor-α and β in papillary thyroid carcinoma

Abstract: BackgroundThe incidence of papillary thyroid cancer (PTC) is markedly higher in women than men during the reproductive years. In vitro studies have suggested that estrogen may play an important role in the development and progression of PTC through estrogen receptors (ERs). This study aimed to investigate the expression patterns of the two main ER subtypes, α and β1 (wild-type ERβ), in PTC tissue and their clinical significance.MethodsImmunohistochemical staining of thyroid tissue sections was performed to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
79
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 54 publications
(83 reference statements)
10
79
1
3
Order By: Relevance
“…These isoforms are coded for by distinct genes and are expressed differently in human tissues during morphogenesis and in adult life (21,22). The expression pattern of ER isoforms has been demonstrated in neoplastic and non-cancerous human thyroid tissues; however, the results are not consistent (19,20). Experimental studies have revealed that estrogen affects PTC development by interacting with ER at the level of target thyroid cells, thereby promoting the proliferation of mutated follicular cells (23).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These isoforms are coded for by distinct genes and are expressed differently in human tissues during morphogenesis and in adult life (21,22). The expression pattern of ER isoforms has been demonstrated in neoplastic and non-cancerous human thyroid tissues; however, the results are not consistent (19,20). Experimental studies have revealed that estrogen affects PTC development by interacting with ER at the level of target thyroid cells, thereby promoting the proliferation of mutated follicular cells (23).…”
Section: Discussionmentioning
confidence: 92%
“…There are an increasing number of studies indicating that estrogen may exert a direct effect on tumorigenesis in human thyroid cells by ER-dependent or ER-independent mechanisms, through modulating cell proliferation and regulating the function of the thyroid (8,19,20). The mechanistic evidence for these effects on thyroid function and growth regulation was reviewed by Santin and Furlanetto (8).…”
Section: Discussionmentioning
confidence: 99%
“…Silencing with selective siRNAs of either ERa or ERb showed contrary effects and thus confirmed the stimulation experiments. Very recently, a study of 89 females with PTC, which correlated ER expression with tumor size and proliferation marker Ki-67, reaffirmed the role of ERa in growth stimulation of these tumors and, on the other hand, an inhibitory effect of ERb (Huang et al 2014). …”
Section: Er Expression In Benign and Malignant Thyroid Tissuesmentioning
confidence: 99%
“…As already reported, gender is an age-specific effect modifier for thyroid cancer incidence (29), explained by the different sex hormone pattern between females and male in the prepubertal and postpubertal ages. Estrogen receptors (ER) are present in normal and neoplastic thyroid tissue and estrogen-activated ERα may represent a stimulatory effect for PTC growth and progression (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%